O Ensino Superior durante a pandemia: infraestrutura educacional, práticas pedagógicas e o engajamento dos estudantes - Ferreira, Cláudia Rampazzo Bragança (2023)
This research is part of the Research Line: New Technologies in Education of the Postgraduate Program in Education: Curriculum at the Pontifical Catholic University of São Paulo (PUC-SP). It aims to identify the institutional conditions in higher education that favor pedagogical innovation when adopting remote teaching in order to identify (analyze) if/what were the favorable conditions for student engagement. With a qualitative, exploratory approach, the research carried out a Systematic Literature Review (SLR) of scientific productions in Portuguese produced during the pandemic, using the public databases Portal de Periódicos da CAPES and Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) as the search source. The categories analyzed are: 1) educational management, 2) pedagogical practices, 3) curriculum and 4) affectivity. It also looks at the Online Learning and Fun (OLAF) research, the result of a partnership between PUC-SP and the Open University (OU) in the UK, which investigates what students understand about learning and fun. Data analysis revealed that Higher Education Institutions (HEIs) prioritized educational equity over other issues when offering materials and subsidies for access and permanence in Emergency Remote Education (ERE) classes. The curriculum was readjusted and sought to meet the teaching and learning needs of the context. The new ways of learning and teaching have put a strain on pedagogical practices and prompted new methodological approaches that have favored interaction and affection between students, classmates and teachers mediated by technologies, as well as providing the construction of knowledge by students, motivation and their academic engagement